Relaxamento progressivo, stress, enfrentamento e qualidade de vida em pessoas com apneia obstrutiva do sono - Mellado, Cristiane Regina dos Santos Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The progressive relaxation of Jacobson, a technique that seeks to minimize the effect of stress through exercise muscle stiffness and relaxation to apply in behavioral therapy for the treatmento of psychological aspects related to syndrome of Obstructive Sleep Apnea or OSA. The syndrome characterized by the occurence of repetitive events for complete or partial obstruction of the upper airway during sleep. Affects the stress, state that impairs the body's homeostasis, in coping strategies or adaptative responses to stressful situations, and also the quality of life (QOL), individual's perception of this life in accordance with their system of values and culture. Thus, the study sought to evaluate the effect of progressive relaxation on stress and quality of life in people with OSA identify coping strategies reported by the participants before and after the intervention. For this intervention research was conducted with 57 individuals between 24 and 72 years, 32 (56.1%) males and 25 (43,8%) were female. Of these, 44 (77.1%) live in stable relationships and 47 (82.4%) with children. As for education, 32 (56.1%) had a college degree, with five graduate and quite varied professions with higher incidence of retirees, banking, lawyers, contract managers, credit stoves, researchers and home. The assessment instruments used were the Inventory of Stress Symptoms in Adults Lipp, Coping Inventory of Folkman and Lazarus Strategies and WHOQOL-bref the World Health Organization Quality of Life Group. The participants were divided into two groups, G1 being the intervention group with progressive relaxation and G2 control group. The results we received quality and quality treatment showed that 68.4% of participants had stress being, 48.7% in G1 and 51.2% in G2. After, the intervention the symptoms of stress detect in 36.8% of participants in the intervention group (G1) and 56.4% in the control group (G2). The Coping Strategies commonly used before the...

O relaxamento progressivo de Jacobson, técnica que busca minimizar o efeito da tensão por meio de exercícis musculares de enrijecimento e relaxação pode ser aplicado em terapia comportamental para o tratamento dos aspectos psicológicos relacionados à Síndrome da Apneia Obstrutiva do Sono ou SAOS. A referida síndrome caracteriza-se pela ocorrência de eventos repetitivos de obstrução total ou parcial das vias aéreas superiores, durante o sono. Interfere no stress, estado de tensão que desequilibra a homeostase do organismo, nas estratégias de enfrentamento ou respostas adaptativas a situações estressoras, e também na qualidade de vida (QV), percepção do indivíduo sobre a sua vida, em acordo com seu sistema de valores e sua cultura. Assim, o estudo pretendeu avaliar o efeito do relaxamento progressivo sobre o stress e qualidade de vida em pessoas com SAOS e identificar as estratégias de enfrentamento relatadas pelos participantes antes e após a intervenção. Para tanto realizou-se pesquisa de intervenção com 57 indivíduos, entre 24 e 72 anos, sendo 32 (56,1%) do sexo masculino e 25 (43,8%) do sexo feminino. Destes, 44 (77,1%) vivem em união estável e 47 (82,4%) com filhos. Quanto à escolaridade, 32 (53,1%) possuíam curso superior completo, cinco com pós graduação e profissões bem variadas com incidência maior de aposentados, bancários, advogagos, gerente de contratos, recuperadores de crédito, investigadores e do lar. Os instrumentos de avaliação utilizados foram o Inventário de Sintomas de Stress em Adultos de Lipp, Inventário de Estratégias de Coping de Folkman e Lazarus e WHOQOL - bref do Grupo de Qualidade de Vida da Organização Mundial da Saúde. Os participantes foram divididos em dois grupos, sendo G1 o grupo de intervenção com relaxamento progressivo e G2 grupo controle. Os resultados receberam tratamento quantitativo e qualitativo e demonstraram que 68,4% dos participantes apresentaram stress...
Keywords: Avaliação de comportamento; Relaxamento - Aspectos psicologicos; Qualidade de vida; Síndromes da apneia do sono; Behavioral assessment